Determinasi Kinerja Organisasi: Analisis Remunerasi, Pelatihan, Jenjang Karier dan Budaya Organisasi: Human Resource Management - Tubagus Hedi Saepudin; Kamsariaty Kamsariaty; Agus Suhendra; Josua Panatap Soehaditama; Rintis Eko Widodo (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to develop hypotheses related to factors that influence organizational performance, particularly in airline companies. The approach used is descriptive qualitative research with data collection techniques through literature studies, namely by reviewing relevant previous articles published in the 2020-2025 period. The analysis technique used is comparative analysis. The data used comes from relevant previous research, sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4, Emerald, Elsevier, Sage, Web of Science, Sinta Journal 2-5, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of this study indicate that: 1) Remuneration affects organizational performance; 2) Training affects organizational performance; 3) Career paths affect organizational performance; 4) Organizational culture affects organizational performance. In addition, this study also found that external factors such as market changes and industry competition also have a significant impact on organizational performance. This study provides an overview of the importance of these factors in improving organizational performance, especially in airline companies, and the importance of effective human resource management to achieve the organization's strategic goals.